Relationship Analysis Between Monetary Policy and Financial Sustainability in Iraq For the Period 2015–2021 - Sabri Al-Aside, Mohammed; Yahiya Saleh Al- Kubaisi, Lawrence (Journal of Economics and Administrative Sciences, 2023)
This research aims to study and analyze the reality of monetary policy and financial sustainability in Iraq through either a descriptive or analytical approach by trying to link and coordinate between monetary policy and fiscal policy to enhance economic sustainability. The research is based on the hypothesis that the monetary policy of Iraq contributes to achieving financial stability, which improves economic sustainability by providing aid and assistance to the state to reduce the budget deficit and exacerbate indebtedness. The author used the monetary policy indicators, the re-deduction of Treasury transfers by the central bank and the money supply, and financial sustainability indicators, including the public debt indicators and the deficit or surplus to GDP indicator, to prove the role of monetary policy in enhancing the financial sustainability of Iraq and to show that monetary policy plays a role in making Iraq's economy more stable. The study found that there is a role for monetary policy in enhancing financial sustainability, significantly when oil prices decrease in global markets, directly or indirectly, through the use of a set of economic tools, including discounting treasury transfers, the money supply, and the exchange rate. Paper type:  Research paper